Effects of short-term heat stress on the activity of three antioxidant enzymes of predatory mite Neoseiulus barkeri (acari, phytoseiidae) - Li, Wei-Zhen; Zhu, Tong; Zhou, Jing-Jiang; Shang, Su-Qin (Frontiers in Physiology, 2022)
To study the physiological mechanisms of Neoseiulus barkeri in the response to short-term heat stress, the eggs and the emerged adults were treated at 38℃, 40℃ and 42℃, 85% ± 5%RH,16h:8h (L:D) for 2, 4 and 6h. The activities of superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) as well as the protein content of N. barkeri were examined. All treatments caused a significantly different changes from that of untreated control samples. The protein content increased as the temperature increased, while it showed different changing trends as the prolongation of exposure duration. The enzymatic activity of SOD, CAT and POD was significantly affected by the temperature. Both the maximum and minimum level of three enzymes after short-term heat stress had significant difference with the control group (P < 0.05). The highest values of three enzymatic activity were all obtained at 40 ℃-4h. Person correlation analysis indicates that the high temperature was the primary factor affecting the enzymatic activity, while the exposure duration of heat stress was the secondary factor. In general, short-term heat stress increased the protein content of Neoseiulus barkeri, and up-regulated the expression of SOD, CAT and POD activities as well.